Presentation skills of business and economics students: Cluster analysis - Tamara Ćurlin; Mirjana Pejić Bach; Ivan Miloloža (Croatian Review of Economic, Business and Social Statistics (CREBSS), 2020)
Presentation skills are one of the most important tools that are required on numerous occasions in education and business. In most of the business and economics colleagues, presentation skills are taught as part of the curriculum, of at least several courses. Therefore, it could be expected that presentation skills would be highly developed among business and economics students. However, in practice, people develop numerous fears and barriers to the presentation in public. On the other hand, students do not behave in the same manner taking into account their fear towards the presentation in public. The goal of the paper is to investigate if there are homogenous groups of students according to their attitude towards the presentation, both as sources of success and as a source of fear. Cluster analysis has been employed to fulfil the paper goal. Non-hierarchical k-means analysis has been conducted on data collected by the research instrument about the benefits and fears from the presentations on the sample of students enrolled in business and economics colleagues. Results indicate that there are homogenous groups of students according to presentation perceived benefits and fears, but the composition of these groups indicates that perceived benefits and fears of presentations are not always related in the same direction.
Keywords: A23; I23; 330; education; k-means; presentation anxiety; presentation skills